The comparative studies of Borneo plant extracts to increases vaccine efficacy in tilapia, Oreochromis niloticus - Esti Handayani Hardi; Komsanah Sukarti; Maulina Agriandini; Irawan Wijaya Kusuma; Rudi Agung Nugroho (Jurnal Akuakultur Indonesia)
ABSTRACT